A first investigation into gender minority adolescents' sexting experiences. (29th September 2020) - Van Ouytsel, Joris; Walrave, Michel; De Marez, Lieven; Vanhaelewyn, Bart; Ponnet, Koen
ABSTRACT: Introduction: Gender minority adolescents, such as transgender, gender nonconforming, gender diverse and non‐binary youth, may face unique challenges with regard to online sexual communication. They may be especially vulnerable for sexting‐related risks. The aim of this study is to explore the sexting experiences of gender minority youth among a school‐based sample. Methods: This brief exploratory study reports on a survey that was conducted among 1293 respondents with an average age of 14.79 years old ( SD = 1.97) in the Dutch‐speaking area of Belgium, and compares engagement in sexting experiences between cisgender and gender minority youth. Results: The results of our exploratory study show that gender minority adolescents were more likely to have ever been pressured to send a sexting image. There were no significant differences with regard to receiving sexts, or receiving forwarded sexts. None of the gender minority youth reported that they had forwarded a sexting image from someone else, as opposed to 9.3% of cisgender youth who had forwarded a sext. Conclusions: Despite the explorative nature of our study, the results suggest that gender minority youth may be at an increased risk to experience sexting‐related pressure. Additional research is needed to investigate the sexting experiences of gender minority adolescents. Gender minority youth may benefit from education about safer sexting, and specifically ways to cope with sexting‐related pressure.